Creating Instagram Press Releases of Misstika Craft Linked to a Writing Platform - Aisyabella Brilliana Azzahra; Bambang Suryanto; Nugrahaningtyas Fatma Anyassari (Jurnal Linguistik Terapan, 2024)
Misstika Craft is a craft business that intends to thrive internationally. Based on several stages of analysis, the Instagram business of Misstika Craft can potentially become a promotional medium for product knowledge through writing platforms. Therefore, the researcher created promotional Instagram press releases linked to a writing platform as an innovation in promotional media for the business. This research involved the theory of the Press Release Hybrid Genre, which mixes comprehensive business details with supportive promotional elements. Furthermore, the researcher uses visual storytelling theory to create video content. This study attempts to develop a new promotional strategy by merging press releases on Medium.com and video content on Instagram. This study used Design and Development Research methods. The findings of this study are presented in the form of 13 informative-promotional press releases and 5 Instagram narrative video content. The overall responses to this product were generally positive, with scores of 4.4 for press releases and 4.3 for Instagram video content.